Cross‐national epidemiology of panic disorder and panic attacks in the world mental health surveys. Issue 12 (24th October 2016) - de Jonge, Peter; Roest, Annelieke M.; Lim, Carmen C.W.; Florescu, Silvia E.; Bromet, Evelyn J.; Stein, Dan J.; Harris, Meredith; Nakov, Vladimir; Caldas‐de‐Almeida, Jose Miguel; Levinson, Daphna; Al‐Hamzawi, Ali O.; Haro, Josep Maria; et al.
Abstract : Context: The scarcity of cross‐national reports and the changes in Diagnostic and Statistical Manual version 5 (DSM‐5) regarding panic disorder (PD) and panic attacks (PAs) call for new epidemiological data on PD and PAs and its subtypes in the general population. Objective: To present representative data about the cross‐national epidemiology of PD and PAs in accordance with DSM‐5 definitions. Design and setting: Nationally representative cross‐sectional surveys using the World Health Organization Composite International Diagnostic Interview version 3.0. Participants: Respondents ( n = 142, 949) from 25 high, middle, and lower‐middle income countries across the world aged 18 years or older. Main outcome measures: PD and presence of single and recurrent PAs. Results: Lifetime prevalence of PAs was 13.2% (SE 0.1%). Among persons that ever had a PA, the majority had recurrent PAs (66.5%; SE 0.5%), while only 12.8% fulfilled DSM‐5 criteria for PD. Recurrent PAs were associated with a subsequent onset of a variety of mental disorders (OR 2.0; 95% CI 1.8–2.2) and their course (OR 1.3; 95% CI 1.2–2.4) whereas single PAs were not (OR 1.1; 95% CI 0.9–1.3 and OR 0.7; 95% CI 0.6–0.8). Cross‐national lifetime prevalence estimates were 1.7% (SE 0.0%) for PD with a median age of onset of 32 (IQR 20–47). Some 80.4% of persons with lifetime PD had a lifetime comorbid mental disorder. Conclusions: We extended previous epidemiological data to a cross‐national context. The presence of recurrent PAs in particular is associated with subsequent onset and course of mental disorders beyond agoraphobia and PD, and might serve as a generic risk marker for psychopathology.